The transition of maca from neglect to market prominence: lessons for improving use strategies and market chains of minor crops - Hermann, M.; Bernet, T. (2009)
Maca is an edible root crop of the crucifer family endemic to the Puna of the high Andes in Central Peru around Lake Junin, a chilly plateau at 4000 m altitude. Grown in the late 1980s exclusively in its native area, on no more than 50 ha, maca has experienced over the last years a meteoric rise from an overlooked botanical curiosity to Internet notoriety. In this study, the authorsnarrate the economic history of the crop, andexamine the players and processes behind its re-emergence from neglect and under-use.Theyprovide anaccount of maca’s history, and attempt to disentangle the myths from the realities surrounding the crop, its products and protagonists. Theirgoal is to derive broader lessons for the development of value chains for under-utilized crops. The specific objectives of this study are: a) to describe key processes that caused the expansion of maca cultivation and commercialization, b) to identify factors constraining maca market chain development, and c) to assess the effects of market development on rural livelihoods and on maca biodiversity.